Assessing critical success factors for military decision support - Louvieris, Panos; Gregoriades, Andreas; Garn, Wolfgang (My University, 2010)
This paper outlines the application of case-based reasoning and Bayesian belief networks to critical success factor (CSF) assessment for parsimonious military decision making. An important factor for successful military missions is information superiority (IS). However, IS is not solely about minimising information related needs to avoid information overload and the reduction of bandwidth but it is also concerned with creating information related capabilities that are aligned with achieving operational effects and raising operational tempo. Moreover, good military decision making, should take into account the uncertainty inherent in operational situations. Herein, we illustrate the development and evaluation of a smart decision support system (SDSS) that dynamically identifies and assesses CSFs in military scenarios and as such de-clutters the decision making process. The second contribution of this work is an automated configuration of conditional probability tables from hard data generated from simulations of military operational scenarios using a computer generated forces (CGF) synthetic environment.
Keywords: Bayesian belief networks; Case-based reasoning; Critical success factors; Decision making